HUBUNGAN JARAK DENGAN CAKUPAN DETEKSI DINI HEPATITIS B PADA IBU HAMIL DI PUSKESMAS MATRAMAN, TAHUN 2018 - Doni Lasut; Elsa Elsi; Miko Hananto; Rani Sulastri (IAKMI South Tangerang Branch, 2021)
Abstract Background : Hepatitis as an infectious disease and silent infection needs to be taken seriously, therefore the Directorate General of Hepatitis-PISP Sub Directorate of P2P conducts early detection of pregnant women as a risk group so that it does not transmit to the mother’s baby. Objective : This study is a review of studies based on surveillance data conducted at the time of early detection of hepatitis B in pregnant women in the Matraman District Health Center during January 2018 to October 2018. Method : This study uses DDHB surveillance data at the Matraman District Health Center. The analysis was carried out with correlation coverage with the average distance and abstracted with the closest distance analysis. Results : The results of early detection of HBsAg reactive pregnant women obtained 32 pregnant women (2.71%) reactive from 1180 pregnant women who followed DDHB. Based on the distribution of pregnant women coverage in the region varies if the spatial analysis approach is done by calculating the flat distance as confounding which is assessed and found to be more distant urban areas from the location of the Matraman District Health Center, the fewer pregnant women who check their pregnancy. Conclusion : Distance related to the coverage of DDHB in the Matraman District Health Center. This situation needs a more adequate surveillance system . Keywords : Jarak, Hepattitis B, DDHB, HBsAg Abstrak Latar Belakang : Hepatitis sebagai penyakit menular dan bersifat silent infection karenanya perlu ditangai secara serius, oleh karena itu Subdit Hepatitis-PISP Dirjen P2P melakukan deteksi dini hepatitis B (DDHB) pada ibu hamil sebagai kelompok beresiko sehingga tidak menularkan ke bayi yang dikandungnya. Tujuan : Penelitian mendapatkan hubungan jarak terhadap cakupan DDHB bumil di Puskesmas Kecamatan Matraman selama Bulan Januari 2018 hingga Oktober 2018. Metode : Penelitian ini menggunakan data survailans DDHB Puskesmas Kecamatan Matraman. Analisis dilakukan dengan mendapatkan nilai korelasi di antara keduanya.. Hasil : Hasil deteksi dini ibu hamil reaktif HbsAg didapatkan sebanyak 32 ibu hamil (2,71 %) reaktif dari 1180 ibu hamil yang mengikuti DDHB. Berdasarkan distribusi cakupan ibu hamil di wilayah tersebut bervariasi apabila dilakukan pendekatan analisis spasial dengan penghitungan jarak datar didapatkan semakin jauh wilayah kelurahan dari lokasi Puskesmas Kecamatan Matraman maka akan semakin sedikit ibu hamil yang memeriksakan kehamilannya. Kesimpulan : Jarak berhubungan terhadap cakupan DDHB di Puskesmas Kecamatan Matraman. Keadaan ini perlunya sistem survilans yang lebih memadai Kata Kunci : Jarak, Hepattitis B, DDHB, HBsAg